Brill's companion to Horace - Günther, Hans Christian. (Brill's Companions to Classical Studies., 2013)
This volume centres on a detailed analysis of the whole corpus of Horace's work by Edward Courtney ( Satires ), Elaine Fantham ( Epistles I and Odes IV), Hans-Christian Günther ( Epodes , Odes I - III, Carmen Saeculare and Epistles II) and Tobias Reinhardt ( Ars Poetica ). The latter is preceeded by a detailed account of Horace's life and work in general by H.-C. Günther. Two appendices on the transmission of the text (E. Courtney) and style and metre (Peter Knox) conclude the volume. It is aimed at students and scholars of classical and modern literature who seek comprehensive orientation on all aspects of Horace's work. All quotations from Latin and Greek are translated.